NOx trapping and soot combustion on BaCoO3-y perovskite: LRS and FTIR characterization - Milt, Viviana Guadalupe (2005)
The BaCoO3-y perovskite-type mixed oxide is studied for both trapping of NOx and combustion of diesel soot. The starting material consists of a stoichiometric mixture of Ba and Co nitrates. Different crystalline phases are obtained when the solids are calcined at different temperatures (ranging from 400 to 1000°C). After 400°C calcination Ba(NO3)2 and Co3O4 crystalline phases are formed, while after calcination at 700°C the BaCoO3 stoichiometric perovskite is obtained. However, when the temperature is increased to 1000°C, the structure loses oxygen and perovskite BaCoO 2.74 is formed. The solids calcined at 700 and 1000°C show high NOx adsorption capacity, the latter being more effective. This solid shows weak IR bands in the 800 cm-1 frequency region associated with the perovskite structure. After the catalyst interacts with NOx, new bands associated with bulk nitrates and surface NO3- species are observed. Signals associated with surface N-bounded species of the OBaNO2 type could be masked by the intense Ba(NO3) 2 signals. LRS characterization is in agreement with XRD and FTIR results. The Raman signal at 716 cm-1 is associated with the BaCoO2.74 structure while a broad signal at 607 cm-1 appears in samples containing BaCoO3 and BaCoO2.94 phases. Nitrates formed upon NO + O2 treatments show high thermal stability under He atmosphere up to 490°C. However, reductive treatments either under H2 atmosphere or with soot particles cause decomposition of the nitrates at temperatures lower than 400°C. A reaction scheme is proposed involving the participation of perovskite structures, Co3O 4, Ba(NO3)2, BaO and metallic Co particles. The catalyst under study favors the reaction between the soot particles and the trapped NOx species making this system promising for the simultaneous abatement of both contaminants. The addition of K decreases the soot combustion temperature.